2007
DOI: 10.1111/j.1600-0781.2007.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive rash due to the epidermal growth factor receptor inhibitor erlotinib

Abstract: A papulopustular rash occurs in 45-100% of patients undergoing anti-cancer treatment with epidermal growth factor (EGFR) inhibitors. Although the majority of cases involve the face and upper trunk, ultraviolet radiation has not yet been documented to play a major role in inducing or exacerbating symptoms. We describe a 75-year-old man who was being treated with the EGFR inhibitor erlotinib and developed the characteristic rash on unprotected areas of the trunk after photoexposure, while the protected areas (fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Interestingly, the incidence and severity of the skin toxicity have been consistently found to be associated with increased tumor response rate and longer survival when analyzed in the context of well-controlled trials (24)(25)(26)(27)(28)(29). The reasons for such association are unclear and several hypotheses, attributing either a predictive or prognostic role to the skin toxicity, have been proposed but none of them has been proved (12,13,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the incidence and severity of the skin toxicity have been consistently found to be associated with increased tumor response rate and longer survival when analyzed in the context of well-controlled trials (24)(25)(26)(27)(28)(29). The reasons for such association are unclear and several hypotheses, attributing either a predictive or prognostic role to the skin toxicity, have been proposed but none of them has been proved (12,13,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the NCCTG observed that previous reports had described that EGFR inhibitor-induced rashes were exacerbated by sunlight. In particular, Luu et al [ 21 ] described a 75-year-old man who developed a rash from erlotinib only on unprotected areas, whereas sun-protected areas manifested no rash. Such observations suggested that an agent such as sunscreen might play a role in preventing or attenuating the severity of the EGFR inhibitor-induced rash.…”
Section: Treatment Of Egfr Inhibitor-induced Rashmentioning
confidence: 98%
“…Some patients receiving EGFR-targeted agents have been reported to show widespread erythema, infiltration and pustules in sun-exposed areas 19,53,54. One randomized study, N05C4, conducted in the US by NCCTG, has investigated the prophylactic use of SPF60 sunscreen in cancer patients receiving an EGFR-targeted agent as part of their therapy 39…”
Section: Resultsmentioning
confidence: 99%